From geophysics to geodetic datum: updating the NZGD2000 deformation model. Issue 1 (2nd January 2016) - Crook, Chris; Donnelly, Nic; Beavan, John; Pearson, Chris
ABSTRACT: The deformation model is a critical component of New Zealand Geodetic Datum 2000 (NZGD2000), the official reference frame for New Zealand. The model is used to manage the relationship between the NZGD2000 and the global International Terrestrial Reference Frame (ITRF), in which precise geodetic measurements are made. Consequently, the deformation model has a direct impact on NZGD2000 coordinates. With improved knowledge of the secular deformation field and models of significant earthquakes to have affected New Zealand since 2000 now being available, the decision was made to update the deformation model. At the same time, the 14-parameter transformation between ITRFs to be used in New Zealand was officially defined.